2014
DOI: 10.1186/1999-3110-55-20
|View full text |Cite
|
Sign up to set email alerts
|

Involvement of trehalose in hydrogen sulfide donor sodium hydrosulfide-induced the acquisition of heat tolerance in maize (Zea mays L.) seedlings

Abstract: BackgroundTrehalose, a non-reducing disaccharide, which involves in the acquisition of various stress tolerance, while hydrogen sulfide (H2S) is considered as a cell signal molecule, but H2S-induced heat tolerance and involvement of trehalose in plants is still unclear.ResultsIn present study, pretreatment with hydrogen sulfide donor sodium hydrosulfide (NaHS) markedly increased the accumulation of endogenous H2S in maize seedlings under normal culture conditions, which in turn improved survival percentage of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
43
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
3
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 82 publications
(44 citation statements)
references
References 47 publications
0
43
0
Order By: Relevance
“…Trehalose content in wheat leaves was determined following the method described by Li et al (2014) with some modifications. The leaves (1.0 g) were homogenized in 5 mL of 80% (v/v) hot ethanol and centrifuged at 11,500×g for 20 min.…”
Section: Determination Of Trehalosementioning
confidence: 99%
“…Trehalose content in wheat leaves was determined following the method described by Li et al (2014) with some modifications. The leaves (1.0 g) were homogenized in 5 mL of 80% (v/v) hot ethanol and centrifuged at 11,500×g for 20 min.…”
Section: Determination Of Trehalosementioning
confidence: 99%
“…Trehalose content in the second leaves was determined following the method described by Li et al (2014) with some modifications. The leaves (1.0 g) were homogenized in 5 mL of 80 % (v/v) hot ethanol and centrifuged at 11,500×g for 20 min.…”
Section: Determination Of Trehalose Contentmentioning
confidence: 99%
“…[11][12][13][14][15][16][17] Our previous research results also showed that NaHS treatment can improve heat tolerance of tobacco cells, maize and wheat seedlings. 1,[18][19][20][21][22][23][24] Enhancement in antioxidant defense system and osmotic adjustment are common mechanisms of plants adapt to adverse environments including heat stress by scavenging reactive oxygen species (ROS); buffering redox; stabilizing protein, nucleic acid and biomembrane; regulating acidity in cytoplasm. 25,26 Further study showed that SA and NaHS treatment alone or in combination significantly increased the activity of antioxidant enzymes superoxide dismutase (SOD), ascorbate peroxidase (APX), glutathione reductase (GR), catalase (CAT, SA treatment alone inhibited CT activity) and guaiacol peroxidase (GPX), and the content of antioxidants ascorbic acid (AsA) and glutathione (GSH), as well as the accumulation of endogenous osmolytes such as proline, betaine and trehalose in maize seedlings (Fig.…”
mentioning
confidence: 99%